Effectiveness of the Alcoholic Fruits Extract of Ficus Carica L. on Pathogenic Bacteria - Jalal, Mustafa J.; Khalid, Raghda W (American Journal of Biology and Natural Sciences, 2025)
The objective of this article is assess the inhibitory potential of fig fruit extract against several bacterial pathogen. Use of the naturals products for their antimicrobial properties has been interest in the recent past. The aims of this work evaluate the ability of the fruits alcoholic extract of F. carica in eliminating some disease-causing bacteria. The extract was prepared using ethanol as a solvent and it was tested against bacterial strains such as E. coli, Staph. Aureus, P. aeruginosa, S. typhi. The results demonstrated significant antimicrobial activity, indicating fig fruit extract has potential to be used in combating bacterial infections. Study results also revealed that the higher concentration of the extract was more effective in inhibiting bacterial growth, table (1).